2009
DOI: 10.1088/0004-637x/697/2/1578
|View full text |Cite
|
Sign up to set email alerts
|

THE LOW LEVEL OF DEBRIS DISK ACTIVITY AT THE TIME OF THE LATE HEAVY BOMBARDMENT: ASPITZERSTUDY OF PRAESEPE

Abstract: We present 24 µm photometry of the intermediate-age open cluster Praesepe. We assemble a catalog of 193 probable cluster members that are detected in optical databases, the Two Micron All Sky Survey (2MASS), and at 24 µm, within an area of ∼ 2.47 square degrees. Mid-IR excesses indicating debris disks are found for one early-type and for three solar-type stars. Corrections for sampling statistics yield a 24 µm excess fraction (debris disk fraction) of 6.5 ± 4.1% for luminous and 1.9 ± 1.2% for solar-type stars… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 107 publications
7
66
3
Order By: Relevance
“…In these stable systems, our dust flux calculations yield typical values for the dust-tostellar-flux ratio F/F star of 0.1−0.5 at 25 μm and 10−35 at 70 μm after 1 Gyr of simulated dynamical and calculated collisional evolution. These values are broadly consistent with the fluxes detected around solar-type stars with observed excesses at 24 and 70 μm (Habing et al 2001;Beichman et al 2006;Moór et al 2006;Trilling et al 2008;Hillenbrand et al 2008;Carpenter et al 2009;Gáspár et al 2009), although our stable simulations yield very few systems with F/F star (70 μm) ≈ 1−10, probably because of the relatively large masses in our outer planetesimal disks (note that our unstable systems can yield those flux levels). Compared with the more sophisticated models of dust production during planetary accretion of Kenyon & Bromley (2008, our calculated fluxes are larger by a factor of a few, notably at 70 μm.…”
Section: Debris Disk Modelingsupporting
confidence: 89%
See 2 more Smart Citations
“…In these stable systems, our dust flux calculations yield typical values for the dust-tostellar-flux ratio F/F star of 0.1−0.5 at 25 μm and 10−35 at 70 μm after 1 Gyr of simulated dynamical and calculated collisional evolution. These values are broadly consistent with the fluxes detected around solar-type stars with observed excesses at 24 and 70 μm (Habing et al 2001;Beichman et al 2006;Moór et al 2006;Trilling et al 2008;Hillenbrand et al 2008;Carpenter et al 2009;Gáspár et al 2009), although our stable simulations yield very few systems with F/F star (70 μm) ≈ 1−10, probably because of the relatively large masses in our outer planetesimal disks (note that our unstable systems can yield those flux levels). Compared with the more sophisticated models of dust production during planetary accretion of Kenyon & Bromley (2008, our calculated fluxes are larger by a factor of a few, notably at 70 μm.…”
Section: Debris Disk Modelingsupporting
confidence: 89%
“…Observations (mainly with NASA's Spitzer Space Telescope) have shown that roughly 15% of solar-type stars younger than 300 million years have measurable dust fluxes at 24 μm (Gáspár et al 2009) but that this fraction decreases in time and flattens off at ∼3% ). At 70 μm, 16% of stars observable dust and there is no measured decrease in this fraction with age (Trilling et al 2008;Carpenter et al 2009).…”
Section: Comparison Between Our Simulations and Observed Debris Disksmentioning
confidence: 99%
See 1 more Smart Citation
“…(g) Averages of measurements obtained from the Hipparcos parallaxes by van den Heuvel (1969);Maeder (1971); Mathieu & Mazeh (1988); Mazzei & Pigatto (1988); Boesgaard (1989);Tsvetkov (1993); Piatti et al (1995); Claria et al (1996); Hernandez et al (1998); Loktin & Beshenov (2001); Salaris et al (2004); Kraus & Hillenbrand (2007); and Gáspár et al (2009). assumed that log g = 4.437, T eff, = 5770 K and M bol, = 4.75, in conformity with the IAU recommendations (Andersen 1999). As above, we averaged all our estimates to obtain log g (phot) , listed in Col. 5 of Table 4.…”
Section: Referencesmentioning
confidence: 96%
“…The IR luminosity of debris disks thus follows the evolution of the larger bodies, which ultimately supply the mass; the typical life time of debris disks is 100 s of Mys to Gyr (e.g., Gáspár et al 2009Gáspár et al , 2013Carpenter et al 2009). …”
Section: Introductionmentioning
confidence: 99%